2010
DOI: 10.1007/s12026-009-8143-4
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from viral encephalomyelitis: immune-mediated noncytolytic virus clearance from neurons

Abstract: Viral encephalomyelitis is caused by virus infections of neurons in the brain and spinal cord. Recovery is dependent on immune-mediated control and clearance of virus from these terminally differentiated essential cells. Preservation of neuronal function is essential for prevention of neurologic sequelae such as paralysis, seizures and cognitive deficits. Using the model system of Sindbis virus-induced encephalomyelitis in mice, we have shown that immune-mediated clearance of infectious virus from neurons is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 83 publications
1
71
0
Order By: Relevance
“…45,46 The age-dependent virulence of ONNV is typical of alphaviruses and has been described in numerous rodent models of alphavirus infection and pathogenesis. 28,42,[47][48][49][50][51][52][53][54][55] Our results also represent progress in developing a murine model to represent human disease after ONNV infection. The STAT1 KO and A129 mice inoculated s.c. do recapitulate the myositis and tenosynovitis that are probably present in humans, as suggested by findings from human infections with the closely related CHIKV.…”
Section: Discussionmentioning
confidence: 80%
“…45,46 The age-dependent virulence of ONNV is typical of alphaviruses and has been described in numerous rodent models of alphavirus infection and pathogenesis. 28,42,[47][48][49][50][51][52][53][54][55] Our results also represent progress in developing a murine model to represent human disease after ONNV infection. The STAT1 KO and A129 mice inoculated s.c. do recapitulate the myositis and tenosynovitis that are probably present in humans, as suggested by findings from human infections with the closely related CHIKV.…”
Section: Discussionmentioning
confidence: 80%
“…CD8 ϩ T cells play a critical role in clearance of viruses from the CNS (10,89,90). CD8 ϩ T cells can control viral infection directly by inducing apoptosis of virus-infected cells via perforin, granzyme, or Fas-FasL interactions (63,91) or indirectly by immunemediated noncytolytic clearance of viruses from neurons by producing cytokines, such as TNF-␣ and IFN-␥ (89,90).…”
Section: Discussionmentioning
confidence: 99%
“…Although perforin-mediated cell killing is a primary strategy to eliminate virus from rapidly dividing and renewable cell types, neurons are generally nonrenewable, and thus it has been proposed that these cytolytic strategies may be more harmful than beneficial within the brain. For a number of viral model systems, it has been shown that cytokine-mediated, noncytolytic strategies control many neurotropic infections (40)(41)(42)(43)(44)(45)(46)(47). These data suggest that the mechanisms by which viral infections are resolved are exquisitely cell type specific and may reflect evolutionary pressures to restrict an infection while minimizing cytopathology and tissue damage.…”
Section: Discussionmentioning
confidence: 99%